Anxiety, depression, and loneliness as key predictors of sleep disturbances in hypertensive elderly - Nguyen, Van Thong; Nguyen, Thang; Nguyen, Tuan Van; Ly, Lan Chi; Nguyen, Tuyen Thi Hong; Nguyen, Tan Dat (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Background: Poor sleep quality is common and is associated with chronic diseases, mental health problems, and reduced quality of life. However, limited evidence exists regarding sleep quality and its potential risk factors among elderly patients with hypertension.Objective: To assess demographic and health-related factors associated with sleep disturbances in elderly patients with hypertension.Methods: A cross-sectional survey was conducted among 414 hypertensive patients aged ≥60 years who received treatment at the Geriatrics Department, Can Tho Central General Hospital, from March 2020 to February 2022. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), with poor sleep quality defined as a global PSQI score >5. Additional data were collected on demographic and mental health factors. Logistic regression models were applied to identify factors associated with sleep quality using odds ratios (ORs), and ROC curve analyses were performed to evaluate predictive factors for sleep disturbances in this population.Results: Among 414 elderly hypertensive patients, the mean PSQI score was 9.72, with 86.5% classified as having poor sleep quality. Older age (≥75 years) significantly increased the risk of sleep disturbance (OR = 1.9, p = 0.037). Depression (OR = 7–11, p < 0.001), anxiety (OR = 7.7, p < 0.001), and loneliness (p < 0.001) were strongly associated with poor sleep quality, while low quality of life markedly increased the risk (OR = 4.7, p < 0.001). ROC analysis showed that the Hamilton Anxiety Scale (AUC = 0.797) and GDS-30 (AUC = 0.748) had the best predictive value, followed by loneliness (AUC = 0.711).Conclusions: Poor sleep quality is highly prevalent among elderly patients with hypertension. Psychological factors, particularly anxiety, depression, and loneliness, are stronger predictors than demographic or clinical variables, highlighting the need for mental health screening and integrated interventions to improve sleep quality in this population.